2009
DOI: 10.1080/03031853.2009.9523824
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HIV/AIDS on food security and household vulnerability in Swaziland

Abstract: This study investigated the impact of HIV/AIDS on food security and household vulnerability in Swaziland. Personal interviews with 847 selected farming households revealed an increase in sales of crops and livestock to finance funerals and healthcare, a decrease in expenditure on agricultural inputs, and an increase in expenditure on medical bills and funerals. Most households were vulnerable to food insecurity. The affected households therefore need assistance in order to maintain food production and security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 3 publications
7
17
0
Order By: Relevance
“…Household labour is being diverted to caring for the sick, and skilled people die or fall sick living behind people with little or no skill on production. This has resulted in more households falling below the poverty line (Masuku & Sithole, 2009). Climate change is another threat faced by households in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Household labour is being diverted to caring for the sick, and skilled people die or fall sick living behind people with little or no skill on production. This has resulted in more households falling below the poverty line (Masuku & Sithole, 2009). Climate change is another threat faced by households in the country.…”
Section: Introductionmentioning
confidence: 99%
“…HIV and AIDS is one of the serious threats to livelihood with more than 40% of the population infected with the pandemic. Masuku and Sithole (2009) reported that there was a positive relationship between HIV and AIDS and food insecurity in the country, and that people were selling livestock as a means of sustenance and to pay medical bills and post death expenses. Crop production has gone down due to a decline in land utilisation, as inputs become unaffordable when the sick or dead member was the one providing finance for inputs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Swaziland life expectancy decreased to 48 years, enlisting it among the lowest in the world; and orphaned and vulnerable children [OVC] were estimated at 104,026 in 2010 [5]. HIV also threatens food security [6,7] because of the increased demand of agricultural produce explained by the cyclical relationship between HIV and nutrition [8]; yet agricultural activities may be deserted due to ill health. For agroeconomy countries, such as Swaziland, poverty is worsened [9], and socio-economic gains reverse [10], putting a question to the long-term survival of such countries [11].…”
Section: Global Burden Of Hiv Infectionmentioning
confidence: 99%
“…Traditionally, T helper cells are thought to differentiate into distinct subsets as Th1 and Th2 with different functions and patterns of cytokine secretion [6]. An imbalance in Th1/Th2 subsets is implicated in resistance and susceptibility to infection [2], the pathogenesis of autoimmune diseases including diabetes mellitus [8], the development of atherosclerosis [86], and hypertensive kidney disease [6]. More evidence suggests that T helper cells have a subset that produces a unique cytokine, IL-17 [99] which has been implicated in the pathogenesis of many autoimmune and inflammatory diseases, and evidence supports that IL-17 has a role in cardiovascular diseases [56].…”
Section: Hiv Art and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation